Traditional and Complementary Medicine - Mordeniz, Cengiz (IntechOpen, 2019)
Modern medicine has reached a point where the patient is not treated as a biopsychosocial-spiritual being but rather is seen as a virtual identity consisting of laboratory findings and images. More focus is placed on relieving the symptoms instead of curing the disease. Mostly, patients are turned into lifetime medication-dependent individuals. New medicines are needed to overcome the side effects, complications, resistance, and intolerance caused by pharmacological and interventional therapies. In hopes of drug-free and painless alternative treatments with fewer complications, there has been a trend to revisit traditional methods that have been dismissed by modern medicine. Traditional medicine has to be reevaluated with modern scientific methods to complement and integrate with evidence-based modern medicine.